Directed ortho-Metalation of Arenesulfonyl Fluorides and Aryl Fluorosulfates - Talko, Alicja; Antoniak, Damian; Barbasiewicz, Michał (Synthesis, 2019)
Studies on directed ortho-metalation (DoM) of arenesulfonyl fluorides (ArSO2F) with in situ electrophile trapping are presented. Under optimized conditions (LDA, THF, –78 °C), a series of model substrates was mono- and difunctionalized with trimethylsilyl chloride in good yields. The synthetic results reveal powerful directing character of the SO2F group, being ahead of bromine and methoxy substituents. Under the same metalation conditions, aryl fluorosulfates (ArOSO2F) display fragmentation to arynes and migration of the SO2F group to the ortho position (anionic thia-Fries rearrangement).
Keywords: sulfonyl fluorides; fluorosulfates; directed ortho-metalation; SuFEx; orthogonal reactivity; in situ trap; lithium amides; anionic thia-Fries rearrangement